SEMICONDUCTOR ELEMENT AND SEMICONDUCTOR DEVICE - SAITO YOSUKE; ICHIMURA MARI; UJIIE YASUHARU; NEGISHI YUKI (2024)
A first semiconductor element according to an embodiment of the present disclosure includes: a first electrode; a second electrode disposed opposite the first electrode; and an organic semiconductor layer disposed between the first electrode and the second electrode and including an organic semiconductor material, a powder of which has a crystal density greater than 1.26 g/cm3 and less than 1.50 g/cm3 by X-ray structural analysis, and which has a molecular weight of 1200 or less and is suitable for vacuum deposition film formation. 根据本公开实施例的第一半导体元件包括：第一电极；第二电极，其布置成与第一电极相对；以及有机半导体层，其设置在第一电极和第二电极之间并且包括有机半导体材料，该有机半导体材料的粉末通过X射线结构分析具有大于1.26g/cm3且小于1.50g/cm3的晶体密度，并且该有机半导体材料具有1200以下的分子量且适用于真空沉积成膜。